2021
DOI: 10.28991/cej-2021-03091637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concrete with Partial Replacement of Cement by Waste Marble Powder

Abstract: This study aims to evaluate concrete having Waste Marble Powder (WMP) as partial replacement of cement. Marble is the metamorphic form of limestone (CaCO3) and WMP was chosen as substitute of cement on account of its high calcium oxide content. WMP is by-product of marble industry and is an environmental burden. The manufacturing of cement is also environmentally hazardous owing to emission of greenhouse gases. Thus, the recycling of WMP in place of cement in concrete offers two ecological advantages. Thirdly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similar our results, different studies showed that adding RHA 70 , NS 71 73 and NA 54 , 74 reduced the workability of the concrete. Furthermore, the incorporation of nanoclay 75 and marble dust powder 76 , 77 makes concrete mixtures stiffer, adversely influencing the workability of concrete. In addition, the workability of concrete containing recycled coarse aggregates (RCA) decreased as the percentage of RCA increased 78 , 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar our results, different studies showed that adding RHA 70 , NS 71 73 and NA 54 , 74 reduced the workability of the concrete. Furthermore, the incorporation of nanoclay 75 and marble dust powder 76 , 77 makes concrete mixtures stiffer, adversely influencing the workability of concrete. In addition, the workability of concrete containing recycled coarse aggregates (RCA) decreased as the percentage of RCA increased 78 , 79 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, researchers' admired trend has been to incorporate waste from marble industries in fired clay bricks. According to Sutcu et al (2015), the increase in percentage addition of marble powder in clay bricks decreases the thermal conductivity to 0.401 W/mK from 1.014 [14,15]. The optimum compressive strength was achieved at a replacement level of 5%, around 93.9% of the control specimen at the heating temperature of 105 0 C. Munir et al [16], the research highlighted that a replacement level of 15% showed satisfactory performance in improving compressive strength.…”
Section: Introductionmentioning
confidence: 98%
“…Concrete is the second most widely used material on earth after water [4]. The widespread use of concrete has led to a global depletion of its raw materials [5]. Moreover, the production of concrete accounts for 5-8% of human-caused CO 2 emissions [6] and is a significant contributor to the emission of greenhouse gases [7].…”
Section: Introductionmentioning
confidence: 99%